The effectiveness of Solanum ferox and Zingiber zerumbet extracts on the survival of Penaeus monodon in different salinity levels of the cultivation media - Hardi, Esti Handayani; Zaidan Fadhilah, Raviv; saptiani, Gina; Fujaya, Yushinta; Suwinarti, Wiwin (Jurnal Akuakultur Indonesia, 2026)
Decreasing the salinity of the water in the cultivation shrimp disease outbreaks, sluggish development, and mortality. Rainfall, water pollution, and climate change lower salinity. Thus, efforts to enhance tiger shrimp that can survive high salinity changes must be anticipated. This study will examine the effect of adding Solanum ferox and Zingiber zerumbet extracts to diet to improve tiger shrimp adaption at 10, 15, and 20‰ salinities. Penaeus monodon (0.017 ± 0.005 g) were randomly dispersed into nine boxes (1×0.5×0.8 m3) with 200 shrimp per container and three replicates per group. The shrimp were fed 1:1 extract, S. ferox (400 ppm), and Z. zerumbet (200 ppm) for 40 days. The study found that adding 5 mL of extract to the feed significantly increases shrimp body weight, weight gain, and specific growth rate at different salinities (P0.05). At salinities of 10 and 15‰, the total bacteria and Vibrio bacteria in culture media and shrimp were lower than at 20‰ (P